REDUCE CO ON CAR BY USING ZEOLITE - MIFTAH FARHANA; Budiyono Budiyono; Nikie Astorina Yunita Dewanti; Wahyu Bambang Widayatno (Pusbindiklat - LIPI, 2020)
The number of vehicles in Jakarta increased by 5.66% from 2016. Vehicles have the highest contribution to air pollution, which is 70% of other activities. The purpose of this study was to determine the reduction of CO with zeolite pellets. This type of research is a quasi-experimental design with a non-equivalent control group design pre-test post-test design. The emission test instrument uses the automotive gas analyzer HESBOHN, a tachometer to measure engine speed, laptops, and stopwatches. The material used is activated natural zeolite pellets. Data were analyzed by univariate in the form of CO adsorption power efficiency, average, minimum, and maximum. The variables used are pellet drying time (3 hours and 24 hours) and engine speed (idle and 1250 rpm). The result of CO adsorption power efficiency using the most optimal zeolite pellets is Pellet I with 3 hours drying at 1250 rpm by 52%. While the lowest yield is Pellet II with 24-hour drying at idle conditions of 22%. The most effective CO emission reduction is by using Pellet I at 1250 rpm.